PENGARUH PENAMBAHAN KARBON AKTIF DARI KULIT SINGKONG TERHADAP PENURUNAN KADAR MANGAN (Mn) DALAM AIR DENGAN BEBERAPA VARIASI KONSENTRASI - Darmawati Darmawati; Syarifah Maulidar; Khairun Nisa (Biotik, 2019)
The study aims to find out about the possibility of utilizing cassava peel waste as raw material for making activated carbon to reduce levels of Manganese in water. This study also wants to see the effect of variations in the concentration of activated carbon from cassava peels on decreasing levels of Manganese in water. This research was conducted at the Laboratory of the Akademi Analis Kesehatan Pemerintah Aceh and at the UPTD Laboratorium Kesehatan Banda Aceh on 3-11 March 2016. Manganese was analysed using the persulfate method while the Manganese was examinated by the spectrophotometric method. The sample used is an artificial sample by adding MnSO4 to water. The variation of activated carbon concentration added is 2 gr, 3 gr, and 4 gr. The results are that with the addition of 2 grams of activated carbon the percentage of Manganese reduction was 70.37%, the addition of 3 grams of activated carbon decreased Manganese concentration by 86.59%, while the addition of 4 grams of activated carbon reduced the percentage of Manganese to 92.33%. It can be concluded that the higher the concentration of activated carbon added, the higher the decrease in levels of Manganese in the water.